PENGARUH TINGKAT PENDIDIKAN DAN PEKERJAAN ORANG TUA TERHADAP JUMLAH KARIES GIGI SISWA ANAK SEKOLAH DASAR - Dwi Eni Purwati; Almujadi , (Jurnal Kesehatan Gigi, 2017)
TITLETHE IMPACT OF EDUCATIONAL LEVEL AND PARENTAL OCCUPATION TO DENTAL CARIES PREVALENCE IN SCHOOL CHILDRENABSTRACTTooth disease that often attack by almost all Indonesian’s society is Tooth Caries. Tooth Caries is disease that often found at all social level from Indonesia’s society, whether from the male society, female society and the children. Healthy life behavior can be influenced by economical social someone. Based on that case researcher interest to know is there any influence of social economic’s parent against to tooth caries on child at Muh Sambisari Primary School. Result of the examination at 8 school children on average having 2 decay at Muh Sambisari Kalasan Primary School. The problem follow The Influence of Education and Job of Parent Against to Tooth Caries on Child at Muh Sambisari Primary School. The purpose of research: Known about Influence of Education and Job of Parent Against Parent Against to Tooth Caries on Child At MuhSambisari Primary School. Plan of the research: cross sectional. Type of the research: Analytic. Collecting data technic: observational and survey. Sample : 60 children, (random sampling) at 3rd,4th, and5th grade, Analysis data : Wilcoxon Test..Result of the research Asymp. Sig is 0,019, therefore statistically show that there is meaningful influence between last education degree’s of the parents to the amount of tooth caries on student at MuhSambisari Primary School, and Asymp. Sig is 0,027, therefore statistically show that there is meaningful influence between job degree’s of the parents to the amount of tooth caries on student at MuhSambisari Primary SchoolResults of the research conclude that there is significant influence education degree’s of the parents to the amount of tooth caries on student. There is significant influence between last job degree’s of the parents to the amount of tooth caries on student. Keywords : Educational degree and job of parents, Tooth Caries